ANALISIS NILAI RELIGIUS DALAM FILM NEGERI 5 MENARA YANG DIADAPTASI DARI NOVEL AHMAD FUADI - Novrizal Ardiansyah; Yunas Sabri; Rochmat Tri Sudrajat; Fadillah Muslim; Ricky Surya Aprian (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2018)
Researchers choose the title aims to examine the value that contained in the “Negeri 5 Menara” movie directed by Affandi Abdul Rachman, given from Ahmad Fuadi’s novel and made by Million Picture. This research aims to describe the religious values that contained in the movie. This study applied descriptive qualitative method and discourse analysis method model Van Djik. “Negeri 5 Menara” movie has a religious value that exemplary by the readers. The result shows that the values can be made as motivation for the readers in daily life such as sincere, patient, gratitude, forgiving, relationship, dutiful to parent, and hard work in studying.